2017
DOI: 10.1371/journal.pone.0170078
|View full text |Cite
|
Sign up to set email alerts
|

Combination of anti-L1 cell adhesion molecule antibody and gemcitabine or cisplatin improves the therapeutic response of intrahepatic cholangiocarcinoma

Abstract: Cholangiocarcinoma has a poor prognosis and is refractory to conventional chemotherapy and radiation therapy. Improving survival of patients with advanced cholangiocarcinoma urgently requires the development of new effective targeted therapies in combination with chemotherapy. We previously developed a human monoclonal antibody (mAb) Ab417 that binds to both the human and mouse L1 cell adhesion molecule (L1CAM) with high affinities. In the present study, we observed that Ab417 exhibited tumor targeting ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 29 publications
(41 reference statements)
2
14
0
Order By: Relevance
“…It has been shown that L1CAM expression confers increased cell growth and tumorigenesis of colorectal cancer cells ( 26 ). Further along this line, a combination of anti-L1CAM antibody and cisplatin was found to improve the therapeutic response in cholangiocarcinoma by enhancing tumor growth inhibition compared to treatment with the drug alone ( 27 ). Recently, Jo et al showed that L1CAM increased the adhesion-mediated proliferation and resistance of Y-79 and SNUOT-Rb1 RB cells to carboplatin, vincristine and etoposide ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that L1CAM expression confers increased cell growth and tumorigenesis of colorectal cancer cells ( 26 ). Further along this line, a combination of anti-L1CAM antibody and cisplatin was found to improve the therapeutic response in cholangiocarcinoma by enhancing tumor growth inhibition compared to treatment with the drug alone ( 27 ). Recently, Jo et al showed that L1CAM increased the adhesion-mediated proliferation and resistance of Y-79 and SNUOT-Rb1 RB cells to carboplatin, vincristine and etoposide ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The studies summarized above point to the numerous genes that are induced (and suppressed) during CRC progression following L1 expression. Because the level of L1 expression was shown to be a powerful prognostic factor for indicating poor survival in a variety of cancer types, L1 is considered a promising target for cancer therapy that involves blocking L1 antibodies in combination with cytostatic drugs and/or radio-immunotherapy [ 67 , 68 , 69 , 70 ]. The downstream target genes of L1-mediated CRC progression described here could mimic the effects conferred by L1 on the motile, tumorigenic, and metastatic properties of CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…[54][55][56][57] Since L1 expression in various types of cancer confers a profound resistance to chemotherapy, antibody-mediated blockade of L1 in combination with cytostatic drugs, or applied as radio-immunotherapy, has already proven to be an excellent strategy for the efficient reduction of tumor burden in several preclinical studies. [58][59][60][61] These promising preclinical results, together with the association of L1 expression with CSC properties and its important roles in cancer initiation, metastasis and therapy resistance, strongly support the suitability and great potential of L1 as a therapeutic target for improving the treatment of metastatic and drug-resistant tumors. Accordingly, considerable efforts are already underway to evaluate the efficacy of L1 blockade in clinical trials.…”
mentioning
confidence: 85%
“…Considering the multifaceted roles of L1 in these diverse fundamental steps during tumor initiation and progression (Figure 1), it is perhaps not surprising that L1 was shown to be a powerful prognostic factor indicating poor survival of cancer patients 18,50‐53 and is regarded as a promising target for cancer therapy 54‐57 . Since L1 expression in various types of cancer confers a profound resistance to chemotherapy, antibody‐mediated blockade of L1 in combination with cytostatic drugs, or applied as radio‐immunotherapy, has already proven to be an excellent strategy for the efficient reduction of tumor burden in several preclinical studies 58‐61 . These promising preclinical results, together with the association of L1 expression with CSC properties and its important roles in cancer initiation, metastasis and therapy resistance, strongly support the suitability and great potential of L1 as a therapeutic target for improving the treatment of metastatic and drug‐resistant tumors.…”
Section: Figurementioning
confidence: 99%